2008
DOI: 10.1080/15287390701738467
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat-Induced Apoptosis in Human Neuroblastoma SH-SY5Y Cells: Involvement of p53 and Mitochondria

Abstract: The herbicide paraquat is a suspected etiologic factor in the development of Parkinson's disease (PD). Paraquat was therefore used to reproduce Parkinsonian syndromes in lab animals, in which it produces dopaminergic pathogenesis. However, the factors or mechanisms by which paraquat kills dopaminergic neurons are not fully understood. Based on reported evidence that paraquat increases p53 protein levels and inhibits mitochondrial function, it was hypothesized that paraquat induces cell death in dopaminergic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 91 publications
7
49
0
Order By: Relevance
“…Paraquat (N,N′-dimethyl-4,4′-bipyridinium dichloride) is a widely used herbicide that is toxic to kidney cells and functions to increase ROS levels in humans and animals through the inhibition of mitochondrial function. [32][33][34][35] Like that observed with Y 2 O 3 NPs, we found that the paraquat exposure induced a similar MTT response ( Figure 3C). The mechanism of the paraquat and the Y 2 O 3 NP cytotoxicity are similar but is not currently clear and will require further in-depth experimentation.…”
Section: Discussionsupporting
confidence: 62%
“…Paraquat (N,N′-dimethyl-4,4′-bipyridinium dichloride) is a widely used herbicide that is toxic to kidney cells and functions to increase ROS levels in humans and animals through the inhibition of mitochondrial function. [32][33][34][35] Like that observed with Y 2 O 3 NPs, we found that the paraquat exposure induced a similar MTT response ( Figure 3C). The mechanism of the paraquat and the Y 2 O 3 NP cytotoxicity are similar but is not currently clear and will require further in-depth experimentation.…”
Section: Discussionsupporting
confidence: 62%
“…Thus, oxidative cellular stress by PQ involves both the generation of reactive oxygen species (ROS) and mitochondrial dysfunction. The mitochondrial pathway of apoptosis has been suggested as one of the mechanisms for dopaminergic neuronal cell death by PQ (Yang and Tiffany-Castiglioni, 2008). Recently, many mechanisms of cell death other than apoptosis have been revealed .…”
Section: Introductionmentioning
confidence: 99%
“…58 Moreover, paraquat and rotenone induce cytochrome c release 59,60 and caspase-9 activation, which are preceded by the induction/ activation of proapoptotic Bax and Bak. 61 In addition, it has been observed that 4-HT pretreatment successfully inhibited the plumbagin and juglone induced accumulation of Bax in the mitochondrial membrane, cytochrome c release, as well as caspase-3 activation in human peripheral blood lymphocytes. 63 To our knowledge this is the first report about the 4-HT mediated attenuation of various molecules involved in the cell cycle arrest and apoptotic microglial cell death induced by dichlorvos.…”
Section: -Ht Pretreatment Attenuates the Dichlorvos Mediated Change mentioning
confidence: 99%